Treatment of acute ischemic stroke with recombinant tissue plasminogen activator: practice pattern among neurologists and physicians - Mohammed, Yaseen; N., Sarala; B., Asha; K., Bhuvana (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Stroke is an abrupt onset of a neurologic deficit due to a focal vascular disease. Treatment guidelines for acute ischemic stroke (AIS) within 4.5 hours of onset are thrombolysis with recombinant tissue plasminogen activator (rtPA). To determine the practice pattern of rtPA in the treatment of acute ischemic stroke among consultants using a questionnaire. Methods: A questionnaire based study was carried out from May to September 2015. Neurologists and physicians from Kolar and Bengaluru were given a questionnaire comprising of 21 questions, regarding the treatment of AIS with rtPA. The data was analyzed using descriptive statistics. Results: A total of 76.9% responded to the questionnaire, of which 18 were neurologists and 82 were physicians. An average of 4-5 AIS patients per month were seen by the doctors. Majority (72%) did not use rtPA, due to delay in patient reaching hospital or non-affordability of the drug. The consultants (66%) opined that rtPA was the best if patient arrived within 4.5 hours of onset of AIS. Only 34% consultants knew the correct score of AIS for administration of rtPA. The usage of penumbral imaging before thrombolysis was agreed by neurologists (58%) and physicians (34%). The IV+IA rtPA thrombolytic therapy produced highest rate of recanalization as expressed by neurologists (84%) and physicians (56%). Majority (80%) felt that use of rtPA beyond 4-6 hours had no beneficial effect. The adverse effects encountered were hypotension and bleeding. Conclusions: Neurologists and physicians opined that treatment with rtPA was effective in patients of AIS within 4.5 hours of onset, but the limitations were late arrival of patient to hospital and drug cost.